Intrapancreatic Ganglia and Neural Regulation of Pancreatic Endocrine Secretion - Li, Wenjing; Yu, Guangjiao; Liu, Yudan; Sha, Lei (Frontiers in Neuroscience, 2019)
Extrapancreatic nerves project to pancreatic islets directly or converge onto intrapancreatic ganglia. Intrapancreatic ganglia constitute a complex information-processing center that contains various neurotransmitters and forms an endogenous neural network. Both intrapancreatic ganglia and extrapancreatic nerves have an important influence on pancreatic endocrine function. This review introduces the histomorphology, innervation, neurochemistry, and electrophysiological properties of intrapancreatic ganglia/neurons, and summarizes the modulatory effects of intrapancreatic ganglia and extrapancreatic nerves on endocrine function.